Utility of Point-of-Care Ultrasound During Prone Positioning Cardiopulmonary Resuscitation - Haris Patail; Tinatin Saralidze; Gabriel Hernandez Romero; Hassan Patail (Case Reports in Critical Care)
This report describes a 34-year-old male admitted to the medical intensive care unit (ICU) who sustained cardiac arrest while in prone positioning. Prone position CPR was initiated, and the utilization of point-of-care ultrasound (POCUS) during CPR was necessary to assess compression quality. Specifically, the popliteal was observed using POCUS to gauge the adequacy of compressions and subsequent perfusion during prone position CPR. This approach provides insight into assessing the effectiveness of chest compressions in a challenging prone position, potentially improving outcomes in similar cases. Further research and application of POCUS in this context may enhance the quality of CPR and patient care during cardiac arrest events in prone positioning.